2008
DOI: 10.1117/1.2992129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early demineralization in teeth using the signal attenuation in optical coherence tomography images

Abstract: Optical coherence tomography imaging is used to improve the detection of incipient carious lesions in dental enamel. Measurements of signal attenuation in images acquired with an 850-nm light source were performed on 21 extracted molars from eight human volunteers. Stronger attenuation was observed for the optical coherence tomography (OCT) signal in healthy enamel than in carious lesions. The measured attenuation coefficients from the two groups form distinct statistical populations. The coefficients obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 17 publications
(2 reference statements)
5
74
0
15
Order By: Relevance
“…However, from in vivo observation of teeth with a clear case history, it was confirmed that carious lesions appeared to have curved lesion front resulting in a bowl shape under OCT, while hypomineralized developmental lesions appeared rather like a horizontal layer. It was reported that WSLs clinically diagnosed as a carious lesion appeared as bowl type by OCT, and a histological section in the same plane after tooth extraction confirmed that shape 28) . On the other hand, hypomineralized developmental lesions visually appear as hypoplastic bands in real clinical situation; their indepth appearance as layers under OCT is due to their developmental nature.…”
Section: Discussionmentioning
confidence: 76%
“…However, from in vivo observation of teeth with a clear case history, it was confirmed that carious lesions appeared to have curved lesion front resulting in a bowl shape under OCT, while hypomineralized developmental lesions appeared rather like a horizontal layer. It was reported that WSLs clinically diagnosed as a carious lesion appeared as bowl type by OCT, and a histological section in the same plane after tooth extraction confirmed that shape 28) . On the other hand, hypomineralized developmental lesions visually appear as hypoplastic bands in real clinical situation; their indepth appearance as layers under OCT is due to their developmental nature.…”
Section: Discussionmentioning
confidence: 76%
“…2B which likely are the lesion areas associated with decay too. There is also another decay marker discussed by ChooSmith et al 56 . She has used OCT attenuation slope to characterize the healthiness of a tooth.…”
Section: Intensity Based Dental Octmentioning
confidence: 99%
“…Otis et al demonstrated improved imaging characteristics of a system operating at 1,310 nm vs. 850 nm. 85 Canadian groups have also devoted their studies to caries research using OCT. 8,[86][87][88] They also used PS-OCT systems; however, they creatively combined polarized Raman spectroscopy (PRS) with OCT in detecting early carious lesions. Raman spectroscopy uses laser excitation and the resulting scattering effect is observed in the target tissues.…”
Section: Applications In Caries Detectionmentioning
confidence: 99%
“…7 Visual examination and probing with a sharp explorer is a rather subjective method depending on the examiner' s experience and training. 8 Early caries detection using optical coherence tomography: a review of the literature Clinical radiology is another widely used method that has poor sensitivity for detecting early carious lesions since the lesions are too shallow and do not provide enough contrast. 9 Furthermore, clinicians need a diagnostic tool that employs nonionizing radiation to aid in caries management and diagnosis and reliably tracks the course of caries lesions over an extended time period in order to determine whether the lesion is active and expanding and requires intervention or if the lesion has been arrested.…”
Section: Introductionmentioning
confidence: 99%